1887 Tex. Gen. Laws 7, ch. 9, Art. 318 - (:unkn) unknown (My University, 1887)
Prohibited any person from carrying on his person, saddle, or in his saddlebags, any pistol, dirk, dagger, slung shot, sword cane, spear, or knuckles made of any metal or any hard substance, Bowie knife, or any other kind of knife manufactured or sold for purposes of offense of defense.
Keywords: CARRY